ANALISIS BAHASA IKLAN PRODUK SKINCARE PADA MEDIA SOSIAL FACEBOOK - Pradana, Deva Arya; Rozi, M. Fahrur; Hermawan, Riky; Saputra, Alvin Rama; Hakim, Faris; Pasha, Achmad Salman; Sholihatin, Endang (Jurnal Membaca Bahasa dan Sastra Indonesia, 2023)
In a marketing activity, a strategy is needed to attract many consumers, one of which is marketing activities through advSosialertising on social media. This research aims to 1) find out the linguistic strategies for skincare product advertisements on Facebook social media and 2) find out the form and purpose of the language used in skincare product advertisements on Facebook social media. The method used in this research is qualitative method. The data techniques used to collect data are documentation and observation. The results of this research are 1) the linguistic strategy for advertising skincare products on Facebook social media, namely using persuasive language that describes and explains the benefits obtained from using this skincare product; and 2) the form and purpose of the language used in advertising skincare products on Facebook social media, namely in the form of uploading informative advertising videos and photos on the Wardah and Neuroskin Facebook accounts with the aim of providing information and persuading readers to be interested in using these skincare products.